2011
DOI: 10.1155/2011/839743
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Circadian Rhythms: A Crucial Factor in the Etiology of Depression

Abstract: Circadian factors might play a crucial role in the etiology of depression. It has been demonstrated that the disruption of circadian rhythms by lighting conditions and lifestyle predisposes individuals to a wide range of mood disorders, including impulsivity, mania and depression. Also, associated with depression, there is the impairment of circadian rhythmicity of behavioral, endocrine, and metabolic functions. Inspite of this close relationship between both processes, the complex relationship between the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 80 publications
1
71
0
Order By: Relevance
“…In depressive disorders, rhythm disruption is associated to illness current status. Studies assessing subjects with depressive disorders suggest that biological rhythms are altered in a lesser extent than BD (Salgado-Delgado et al, 2011;Soria and Urretavizcaya, 2009), which is also observed in our data. Furthermore, a study using a clinical sample of euthymic bipolar patients also showed greater overall biological rhythm disruption than heathy controls (Rosa et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In depressive disorders, rhythm disruption is associated to illness current status. Studies assessing subjects with depressive disorders suggest that biological rhythms are altered in a lesser extent than BD (Salgado-Delgado et al, 2011;Soria and Urretavizcaya, 2009), which is also observed in our data. Furthermore, a study using a clinical sample of euthymic bipolar patients also showed greater overall biological rhythm disruption than heathy controls (Rosa et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Dysregulation of internal and neurobiological rhythms reflects changing patterns of serotonin, norepinephrine and dopamine secretion (Salgado-Delgado et al, 2011). Disruption of internal time can lead to further induction of mood and sleep-wake cycle changes (Robillard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with insomnia, defined as difficulty in initiating or maintaining sleep or experiencing non-restorative sleep, are known to have an increased risk of depression compared with those without insomnia 20,21) . Regular patterns of social behaviors-including bedtime and wake time, social interactions and meal time-have been suggested to affect circadian rhythms 22) , and any disruption of these rhythms could cause depressive symptoms 23,24) . However, relatively few studies have investigated the association between bedtime and depressive symptoms.…”
mentioning
confidence: 99%
“…Disruption of biological rhythm was correlated with cortisol elevation in human (Salgado-Delgado et al, 2011). CCL could also elicit stress and higher level of corticosterone in rats (Tapia-Osorio et al, 2013).…”
Section: Discussionmentioning
confidence: 86%